2013
DOI: 10.3810/psm.2013.09.2022
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Bone Marrow Concentrate: Review and Application of a Novel Intra-Articular Orthobiologic for Cartilage Disease

Abstract: Younger adults, aged < 65 years, increasingly present to their physicians with advanced cartilage disease or post-traumatic osteoarthritis. A number of treatments exist for lessening patient pain and improving patient function. However, many patients are becoming aware of the potential of regenerative therapies and are now seeking solutions to the impaired biology underlying their conditions rather than addressing only their symptoms. Patients do not want to merely lessen their symptoms temporarily with a surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 51 publications
0
51
0
2
Order By: Relevance
“…The use of first-generation biologic injectables, like HA, have been successful in the treatment of patients with painful OA of the knee [1]. PRP represented the second-generation of biologic injectables for multiple musculoskeletal disorders, and was the first of autologous nature.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The use of first-generation biologic injectables, like HA, have been successful in the treatment of patients with painful OA of the knee [1]. PRP represented the second-generation of biologic injectables for multiple musculoskeletal disorders, and was the first of autologous nature.…”
Section: Figurementioning
confidence: 99%
“…In an effort to correct the disordered biology, orthobiologics have emerged both as injectable therapeutic options at the bedside and as adjuncts to surgical strategies. Orthobiologics pertain to therapeutic injectables which aim to restore the biologic environment and/or structural components of diseased or damaged musculoskeletal tissue [1]. Cell-based orthobiologic injection therapies today include platelet-rich plasma (PRP) and bone marrow concentrate (BMC).…”
Section: Introductionmentioning
confidence: 99%
“…BMC thus possess anti-inflammatory, angiogenic and immunomodulatory properties that can potentially enhance cartilage repair. 83 Basic science and animal model studies have reported promising results for using BMC in treating cartilage pathology. 84,85 These preclinical trials have led to a few small clinical studies.…”
Section: Autologous Bone Marrow Concentrate (Bmc)mentioning
confidence: 99%
“…This paracrine activity of MSCs is thought to be one of the major means by which these cells mediate anti-inflammatory, anti-apoptotic, antifibrotic, angiogenic, mitogenic, and wound-healing properties that have proliferative effects on cells. 42,44,62,83 The study by Cassano et al 119 reviewed the growth factor and cytokine levels between PRP and BMC. They found that BMC had 172.5x the concentration of vascular endothelial growth factor (VEGF), 78x the concentration of interleukin-8 (IL-8), 4.6x the concentration of interleukin-1beta (IL-1 β), 3.4x the concentration of transforming growth factor-β 2 (TGF-β 2 ) and 1.3x the concentration of platelet derived growth factor (PDGF).…”
mentioning
confidence: 99%
“…A wide spectrum of treatments are available, from non-pharmacological modalities to dietary supplements and pharmacological therapies, as well as minimally invasive procedures involving injections of various substances aimed at restoring joint homeostasis and providing clinical improvement and possible disease modifying effects [34][35][36][37][38][39][40][41][42][43][44][45] . These injections are sometimes painful and are oftentimes combined with local anesthetics to alleviate the discomfort of the injection.…”
Section: Anti-inflammatory Effects Of Prpmentioning
confidence: 99%